Altered glycosylation profiles of serum IgG in Takayasu arteritis - Liu, Lingyu; Li, Jing; Yang, Yunjiao; Hu, Chaojun; Tian, Xinping (European journal of medical research, 2023)
Takayasu arteritis (TAK) is an autoimmune inflammatory disorder with an undefined etiology. This study aimed to characterize the glycosylation profiles of serum immunoglobulin G (IgG) in patients with TAK. Lectin microarrays containing 56 types of lectins were used to detect the glycan levels of serum IgG in 164 patients with TAK, 128 patients with atherosclerosis used as disease controls (DCs), and 100 healthy controls (HCs). Differentially altered glycosylation patterns between TAK and control groups as well as between TAK subgroups were identified and further validated by lectin blot. The classification performance of the TAK-specific glycosylation change was measured by receiver-operating characteristic (ROC) curve analysis. Lectin microarray analysis revealed significantly increased N-Acetylgalactosamine (GalNAc) levels in the TAK group compared to the DC and HC groups (all p < 0.01). For TAK subgroups, significantly decreased mannosylation was observed in patients with active TAK compared to patients with inactive disease (p < 0.01). These differences were validated by lectin blot. In addition, GalNAc levels exhibited a considerable potential for discriminating patients with TAK from patients with atherosclerosis, with an area under the curve of 0.749 (p < 0.001), a sensitivity of 71.7%, and a specificity of 73.8%. Serum IgG in patients with TAK displayed disease-specific glycosylation alterations. Aberrant GalNAc glycosylation showed substantial value as a diagnostic biomarker. The potential proinflammatory properties of the abnormal glycans may provide new insights into the role of humoral immunity in the pathogenesis of TAK.